2008
DOI: 10.1007/s10209-008-0130-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the creative drive: investigating paralinguistic voice as a mode of interaction for artists with upper limb disabilities

Abstract: For people with upper limb disabilities visual art is an important activity that allows for expression of individuality and independence. They show remarkable endurance, patience and determination to adapt their remaining capabilities to create visual art. There are significant advantages of digital technologies in assisting artists with upper limb disabilities. Paralinguistic voice recognition technologies have proven to be a particularly promising mode of interaction. Despite these benefits, technological su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Shortly, accord ing to Johnston (2014), th e paralinguistic attributions or non-verbal signs constituted to the users' physical posture, head movement, eye gaze, facial exp ression, and lips setting. Meanwhile, Perera, Eales, and Blashki (2009) addressed that the paralinguistic attribution qualities importantly allo w the expression and engagement. These prove through the expressive vocalizations, such as laughing and exclaiming, and vocal segregates, such as pitch and volume.…”
Section: Resultsmentioning
confidence: 99%
“…Shortly, accord ing to Johnston (2014), th e paralinguistic attributions or non-verbal signs constituted to the users' physical posture, head movement, eye gaze, facial exp ression, and lips setting. Meanwhile, Perera, Eales, and Blashki (2009) addressed that the paralinguistic attribution qualities importantly allo w the expression and engagement. These prove through the expressive vocalizations, such as laughing and exclaiming, and vocal segregates, such as pitch and volume.…”
Section: Resultsmentioning
confidence: 99%
“…While the feedback is different, the underlying approach is still to use the system to accurately evaluate vocal performance and provide unambiguous feedback. Furthermore, there are indications that using these kinds of systems can lead to positive outcomes [1,5,6,7,11]. For example, Perera et al [11] have shown that the use of the voice to create digital art can lead to improved vocal control and [6,7] have provided evidence that abstract audio-visual feedback was effective in encouraging vocalisations of children with Autism Spectrum Disorder (ASD).…”
Section: Speech Therapy Systemsmentioning
confidence: 97%
“…For example, Perera et al [Perera et al 2008] used screen positions to correspond to vocalizations and showed that using voice to create digital art can lead to improved vocal control. Hailpern et al [Hailpern 2008;Hailpern et al 2009] have provided evidence that abstract audio-visual feedback was effective in encouraging vocalizations of children with Autism Spectrum Disorder (ASD).…”
Section: Speech Therapy Interventionsmentioning
confidence: 99%